Gender and Context Matter: Behavioral and Structural Interventions for People Who Use Alcohol and Other Drugs in Africa - Wechsberg, W.M.; van der Drift, I.; Howard, B.N.; Myers-Franchi, Bronwyn; Browne, F.A.; Bonner, C.P.; Carney, T.; Ndirangu, J.; Washio, Y. (2022)
Heavy alcohol consumption and other drug use are prominent across Africa and increase the risk of exposure to violence, HIV acquisition, and other life-threatening injuries. This review synthesizes evidence on alcohol and other drug (AOD) interventions in Africa; evaluates the differences between interventions that do and do not specifically target populations that use AODs; and highlights the impact of comprehensive vs. brief interventions and those that address syndemic issues from a gender and contextualized lens. Literature searches were conducted to identify research outcomes of randomized interventions published between January 2010 and May 2022 that address AOD use in Africa. Thirty-five full-text articles were included in this review. Most of the identified research studies were concentrated in a few countries. Most studies were conducted in South Africa. Many of the studies comprised brief interventions. However, the most comprehensive interventions were the most effective for AOD outcomes. Several studies indicated the importance of addressing AOD use alongside gender-based violence, mental health needs, gender roles, and other social determinants that affect health outcomes. Intervening on AOD use and addressing social determinants from a gender and contextually relevant perspective is essential to ensuring the long-term health and well-being of people in Africa.